KAJIAN ESTETIKA MOTIF UKIR KERATON SUMENEP MADURA HASIL AKULTURASI TIONGHOA - Zainor Ahmad (Corak : Jurnal Seni Kriya, 2021)
The legacy of ancient objects is the history that there was a civilization at that time, such as a kingdom which was the center of social and cultural society. should be grateful that the kingdoms of the past can still be appreciated today. As in the architecture of the Keraton Sumenep Madura, it gets acculturation from various cultures, namely the Madurese and Chinese cultures. It is possible that the palace carving art got a touch from China. Not only the motifs are beautiful, but they give meaning to every motif displayed on the ornaments of the Sumenep Palace. But in reality there are still many people who do not recognize the local culture. This problem is interesting to be studied further. This paper aims to describe the aesthetic value contained in the ornamental motifs of the Sumenep Madura Palace which is a motif resulting from the acculturation of Madurese and Chinese cultures. This study uses qualitative research methods to describe the various motifs and meanings of the Sumenep Palace ornaments. To obtain data sources, interviews, field observations, and documentation were carried out. The results of the article describe the aesthetic value of the carving ornaments of the Sumenep Madura Palace, namely the Janggoleng motif pattern from the orchid plant, and the Hong bird which is a Chinese motif with the meaning of peaceful life combined with the Burneh plant motif which is a typical Sumenep Madura motif. Peninggalan benda kuno merupakan sejarah bahwa telah terjadi sebuah peradaban di masa itu, seperti sebuah kerajaan, pusat masyarakat bersosial dan berbudaya. Patut disyukuri kerajaan-kerajaan silam masih dapat diapresiasi hingga saat ini. Arsitektur bangunan Keraton Sumenep Madura mendapatkan akulturasi dari berbagai budaya, yaitu budaya Madura dan Tiongkok. Tidak menutup kemungkinan seni ukir keraton pun mendapat sentuhan dari Tiongkok. Bukan hanya motifnya yang indah namun memberikan makna setiap motif yang ditampilkan pada ornamen Keraton Sumenep. Namun kenyataannya, masih banyak masyarakat yang tidak mengenali budaya lokalnya. Permasalahan ini menarik untuk dikaji lebih dalam. Tulisan ini memiliki tujuan mendeskripsikan nilai estetika yang terkandung dalam motif ornamen Keraton Sumenep Madura yang merupakan motif hasil akulturasi budaya Madura dan Tiongkok. Penelitian ini menggunakan metode penelitian kualitatif untuk menguraikan berbagai motif dan makna ornamen Keraton Sumenep. Untuk memperoleh sumber data, dilakukan dengan wawancara, observasi lapangan, dan dokumentasi. Hasil dari artikel ialah mendeskripsikan nilai estetika dari ornamen ukir Keraton Sumenep Madura, yakni adanya pola motif Janggoleng dari tanaman anggrek, serta adanya burung Hong yang merupakan motif Tionghoa dengan makna kedamaian hidup yang dikombinasikan dengan motif tanaman Burneh yang merupakan motif khas Sumenep Madura.